A Note on Blue Hearing System (BHS) to Develop Speech in Deaf and Mute People - Saxena, Parul (Recent Research in Science and Technology, 2010)
Abstract In this paper, the innovative idea of Blue Hearing System has been presented which is an artificial hearing system. This BHS uses the instrument cochlear implant, a bionic ear, whose working is based on the electromagnetic phenomenon of Induction and another important part of this BHS is the learning to create and expand the vocabulary of the person possessing the cochlear implant instrument. The output of the BHS is the measurement of the responses towards various sounds given by the fellow and by meaningful speech development in him or her.